Development and experimental validation of a partially buckling-restrained brace with dual-plate cores. (December 2021) - Yuan, Yue; Qing, Yuan; Wang, Chun-Lin; Lin, Xuchuan; Zhu, Min
Abstract: A new partially buckling-restrained brace with dual-plate cores (DPBRB) was proposed in this paper to improve the flexural stiffness of an all-steel BRB with a plate core. The core member was composed of two identical and separated plates in parallel. The restraining member consisted of steel channels and steel plates that were assembled with high-strength bolts. The restraining member was located at the periphery of the core member to restrain the edge part of the outside and the inside plates in the core member. The restraining member can be reused and easily disassembled by removing the bolts, which effectively improves the utilization. The test results and numerical simulation indicated that all specimens presented stable energy dissipation capacities and low-cycle fatigue properties. The yield segments exhibited inwards buckling deformation, and the deformations at the ends were more evident than those in the middle. Insufficient stiffness of the end of the restraining member caused large deformation and fatigue fracture of the end of the yield segment. A new all-steel assembled restraining plate was provided. The calculation formula for the design length of the restraining member was given based on the results of finite element analysis. Graphical abstract: Unlabelled Image Highlights: A new buckling-restrained brace with dual-plate cores (DPBRB) is proposed. Test results show that DPBRBs exhibit excellent energy dissipation capacities. A new all-steel assembled restraining plate with a larger flexural stiffness is provided. The calculation formula for the design length of the restraining member is given.